2019
DOI: 10.22441/sinergi.2019.1.009
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Deformation Study on Castellated Steel Beam With Tapered Shape and Hexagonal Openings

Abstract: Castellated steel beam is a beam with a regular section cut into half with a particular pattern and regrouped with welding to increase its height compared to the original. This structure element has been developed in building constructions since many years ago. However, its uniform section along the span will make the modification no longer effective in cantilever structure, unless it has additional adaptation. Therefore, in this study, it is proposed to use a castellated steel beam with a tapered shape to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The next step is to determine the design curvature of the shear walls. There are two design conditions: First, to design on serviceability conditions s = 0.0175 / lw (7) Second, to design in a damage control state s = 0.072 / lw (8) The length of the plastic hinge in the shear wall is determined by ( 9) and (10).…”
Section: Design Displacement Design Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step is to determine the design curvature of the shear walls. There are two design conditions: First, to design on serviceability conditions s = 0.0175 / lw (7) Second, to design in a damage control state s = 0.072 / lw (8) The length of the plastic hinge in the shear wall is determined by ( 9) and (10).…”
Section: Design Displacement Design Profilesmentioning
confidence: 99%
“…However, the beams and columns will be pretty significant when the building is designed without shear walls, and problems will arise at the joints [5]. Furthermore, the presence of the shear wall will affect the building's stiffness so that the lateral forces are not fully borne by the frame structure (columns and beams) [6] [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some parametric studies of CB with circular and diamond-shaped openings were carried out. In [6], the study was performed to optimize its size by considering the ratio of the overall depth of the castellated beam to the depth of opening provided (D/Do) and the ratio of spacing of opening to the depth of opening (S/Do). From their study, they concluded that the CB gives good flexural strength results for the diamond-shaped opening with a size of 0.67 times overall depth of the beam.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Steel is a highly durable and resistant material, and the high strength-to-weight ratio of steel enables it to result in a high load-carrying capacity. A lot of advantages are found such as the strength uniformity, specific sizes from the manufacturer so that the section can be easily fabricated and it has high yield strength for both compressive and tensile strength (Maulana et al , 2019). Structural steel sections are more concerned due to its material that can be produced with various shapes and properties (McKee, 2021; AISC, 2018) and I-beam is the most commonly used steel section (Brakefield, 2020).…”
Section: Introductionmentioning
confidence: 99%